Ammonium Bicarbonate as Nutrient Substitute for Improving Biomass Productivity of Chlorella variabilis. Issue 9 (16th August 2016) - Bhattacharya, Sourish; Soundarya, Ramya; Mishra, Sandhya
Abstract: Sodium bicarbonate was replaced with ammonium bicarbonate, recovered from effluent of the pigment industry, for cultivation of CSMCRI's Chlorella variabilis (ATCC PTA 12198) with enhanced biomass and lipid productivity. Compared to Zarrouk's medium, utilizing ammonium bicarbonate in the medium instead of sodium bicarbonate yielded better biomass and lipid productivity in a shorter production time of 9 d in a 5‐L flask. The modified medium containing ammonium bicarbonate also yielded a higher total content of reducing sugar, which can be used for bioethanol production or as carbon source for further mixotrophic growth of C. variabilis . Abstract : Replacing sodium bicarbonate with ammonium bicarbonate as nutrient for cultivating Chlorella variabilis increases its biomass and lipid productivity and yield of sugar, which can be used for bioethanol production. Thus, ammonium bicarbonate recovered from the effluent streams of the pigment industry can be used for mass cultivation of C. variabilis biomass and biodiesel production.